Cyber threats in mobile healthcare applications: systematic review of enabling technologies, threat models, detection approaches, and future directions - Anayo Chukwu Ikegwu; Uzoma Rita Alo; Henry Friday Nweke (Discover Computing)
Abstract Mobile healthcare (mHealth) delivery has revolutionized the healthcare industry 5.0. With the move toward mHealth, access to healthcare services has gradually increased, allowing individualized treatment routines, and real-time health monitoring. However, cybersecurity threats to mHealth systems also increase as their use increases. The continuous rise of cyber threats has recently affected the healthcare delivery sector. These have caused much financial damage and fears in the past few years. This paper aims to systematically assess and categorize the cyber threats in mHealth applications to guide the industry-wide adoption and prospects. A systematic literature review was carried out between 2018 and 2025 including 40 primary study papers were synthesized out of 24,854 search articles. The study discussed mHealth, trends, features, and main technologies to explore the advancement of mHealth. It presents cyber threats in mHealth applications where the common cyber threats were identified and security challenges such as data compromise, malicious attacks, insecure systems, and user vulnerabilities. We provided mitigation strategies to address the inherent challenges. It further highlights traditional and contemporary and centralized and decentralized detection approaches to cyber threats for effective implementation of patient health data. The findings showed that much work is left undone which we offered in open research prospects. The outlined open research prospects will improve the security and privacy of health-sensitive data against cyber threats. The practical implication of this study is that it will guide all health stakeholders, such as patients, health professionals, agencies, government and policymakers, and researchers, in improving the security and privacy of patients’ data in digital cyberspace.